Fiber To The Home Access Network Planning With Gpon Technology Using Genetic Algorithm Method - Padjodjang, Nadia Mardinensi; Pollo, Don E. D. G; Y. Doo, Samy (Journal of Electrical Engineering and Computer (JEECOM), 2024)
The purpose of this research is to plan the Fiber To The Home access network at a location in the city of Soe, Kupang, East Nusa Tenggara. This planning is done to facilitate the construction of the Fiber To The Home network from the center to the customer. Researchers conducted a design based on ODP sample point data based on MAPS from the company PT Arsenet Global Solution Soe Branch, the results of simulations conducted in Matlab and OptiSystem software. In this study, the best route search was carried out for the construction of the Fiber To The Home network using the Genetic Algorithm method, the results of the best route search obtained the shortest route as far as 1.6646 km from the center to the customer. Also obtained 7 ODP points with ODP routes starting from ODP points 2-3-4-5-6-7-1 with the distance of each point to the point 0.0045 km - 0.1466 km - 0.1361 km - 0.1042 km - 0.4396 km - 0.8305 km - 0.0031 km. The results of the simulation of the genetic algorithm design in matlab will be simulated in the optisystem 7.0 software to get the receiving power and Bit Eror value. The simulation results using optysystem will be a reference for calculations using the Power Link Budget method. The Power Link Budget calculation shows the total attenuation value from the center to the customer of 18.7925 dB with a power margin of 3.2 dB, Bit Eror of 5.64838 x 10-24 and Q Factor of 10.0288. The results of the calculation of attenuation and power margin prove that the planning is said to be feasible because the total planning attenuation results are below the attenuation standard set by the company PT Arsenet Global Solusi which is a maximum of 28 dB, as well as having a power margin value of more than 0 and a BER value that meets the standard.